Safety of radial coronary angiography with uninterrupted direct-acting oral anticoagulant treatment - Tuğba Kemaloğlu Öz; Tayfun Gürol; Nedim Umutay Sarıgül; Utku Arslan; Maryam Kobegenova; Alper Aydın; Özer Soylu; Bahadir Dağdeviren (KARE Publishing, 2019)
Objective: It is not known whether direct-acting oral anticoagulants (DOACs), such as dabigatran, apixaban, and rivaroxaban increase the risk of bleeding complications during or after coronary catheterization. The aim of this study was to investigate the safety of uninterrupted DOAC treatment during diagnostic radial coronary angiography (CAG). Methods: This study included 160 patients who underwent diagnostic radial cardiac catheterization. The 60 patients in the group who were using a DOAC (apixaban, rivaroxaban, or dabigatran) were enrolled in a Group A. Post-procedure results from patients in Group A were compared with those of an age- and sex-matched control group (Group B) that included 100 patients who underwent radial CAG who did not use a DOAC. Results: There was no significant difference in the procedure and compression times, creatinine level, or presence of hypertension, diabetes mellitus, smoking, alcohol use, vascular disease, or congestive heart failure between the 2 groups. During the 1 -month follow-up period, only 1 radial occlusion was registered in the control group (Group B). There was no case of a large hematoma (>5 cm or extending to the forearm), dissection, fistula, perforation, or compartment syndrome. Hematomas smaller than 5 cm were seen in 2 patients (1 in each group). No thrombotic events were observed during follow-up examinations. Conclusion: Performing radial CAG with uninterrupted DOAC treatment appears to carry no risk of increased early or short-term complications. The simple, uninterrupted DOAC strategy is comfortable, easy, and safe.